2023
DOI: 10.1002/mds.29560
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Phenotypic Spectrum of GAA‐FGF14 Sporadic Late‐Onset Cerebellar Ataxia (SCA27B)

Abstract: BackgroundHeterozygous GAA expansions in the FGF14 gene have been related to autosomal dominant cerebellar ataxia (SCA27B‐MIM:620174). Whether they represent a common cause of sporadic late‐onset cerebellar ataxia (SLOCA) remains to be established.ObjectivesTo estimate the prevalence, characterize the phenotypic spectrum, identify discriminative features, and model longitudinal progression of SCA27B in a prospective cohort of SLOCA patients.MethodsFGF14 expansions screening combined with longitudinal deep‐phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 16 publications
11
32
3
Order By: Relevance
“…1 SCA27B due to FGF14 GAA repeats has been identified in ataxia cohorts from various ethnic backgrounds, including French-Canadian, German, Australian, Indian, and French populations. 1,2,[4][5][6][7] Additionally, a family lineage with a monoallelic FGF14 GAA repeat and biallelic RFC1 AAGGG repeats was reported from Chile. 14 Taken together, these findings suggest that FGF14 is implicated in cerebellar ataxia across diverse ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 SCA27B due to FGF14 GAA repeats has been identified in ataxia cohorts from various ethnic backgrounds, including French-Canadian, German, Australian, Indian, and French populations. 1,2,[4][5][6][7] Additionally, a family lineage with a monoallelic FGF14 GAA repeat and biallelic RFC1 AAGGG repeats was reported from Chile. 14 Taken together, these findings suggest that FGF14 is implicated in cerebellar ataxia across diverse ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…patients with late-onset ataxia across diverse ethnic backgrounds. 1,2,[4][5][6][7] The high prevalence of this genetic abnormality highlights the need to identify potential treatment options. One study demonstrated that 4aminopyridine results in symptomatic improvement and thus has therapeutic potential.…”
Section: Introductionmentioning
confidence: 99%
“…30,42 The limited multisystemic involvement in SCA27B was reflected in one study by the overall low burden of non-ataxia features measured by the Inventory of Non-Ataxia Signs scale, which increased only slowly with disease duration. 30 Disease progression in SCA27B, averaging 0.23-0.40 SARA point per year, 30,42 is considerably slower than in other common late-onset genetic ataxias, such as SCA6 (0.80 SARA point/year) 48 and RFC1-related disease (1.30 SARA points/year). 58 The slow disease progression in SCA27B is also reflected in the gradual accrual of functional disability, amounting to only 0.10 FARS stage per year of disease duration.…”
Section: Phenotypic Profile and Disease Progressionmentioning
confidence: 99%
“…[21][22][23]30,31,41,42,50 Some -but not allcases carrying biallelic FGF14 GAA repeat expansions may manifest before the age of 30 and/or have a more severe phenotype. 28,29 The GAA repeat length only appears to correlate weakly with the age at onset, 21,22,30,31,42 in contrast to polyglutamine SCAs. 49 Several factors may account for such weak correlation in SCA27B, including patients' failure to recognise early episodic symptoms, co-occurrence of 'second-hit' neurological disease and medical comorbidities, 30,31 unknown genetic modifiers and possibly brain somatic mosaicism.…”
Section: Phenotypic Profile and Disease Progressionmentioning
confidence: 99%
See 1 more Smart Citation